Are Elite Female Soccer Athletes at Risk for Disordered Eating Attitudes, Menstrual Dysfunction, and Stress Fractures?. Issue 3 (16th July 2015) - Prather, Heidi; Hunt, Devyani; McKeon, Kathryn; Simpson, Scott; Meyer, E. Blair; Yemm, Ted; Brophy, Robert
Abstract: Objective: To determine the prevalence of stress fractures, menstrual dysfunction and disordered eating attitudes in elite female soccer athletes. Design: Cross‐sectional descriptive study. Setting: Female soccer athletes were recruited from a national level youth soccer club, an NCAA Division I university team, and a women's professional team. Participants: Two hundred twenty female soccer athletes with a mean age of 16.4 ± 4 years and BMI of 20.8 ± 2 kg/m 2 completed the study, representing all athletes from the included teams. Methods: One‐time surveys completed by the athletes. Main Outcome Measurements: Height and weight were recorded, and body mass index (BMI) was calculated for each athlete. Athletes reported age of menarche, history of missing 3 or more menses within a 12‐month period and stress fracture. The Eating Attitudes Test (EAT‐26) was used to assess the athlete's body perception and attitudes toward eating. Results: Of the 220 soccer athletes, 3 athletes (1.6%) had a low BMI for their age, and 19 (8.6%) reported stress fractures of the lower extremity. Among athletes who had reached menarche, the average onset was 13 + 1 year; menstrual dysfunction were present in 21 (19.3%). On the EAT‐26, 1 player scored in the high risk range (>20) and 17 (7.7%) scored in the intermediate risk range (10‐19) for eating disorders. Athletes with an EAT‐26 score ≥ 10 points had a significantly higher prevalence of menstrual dysfunction in the past year compared to athletes with an EAT‐26 score of less than 10 ( P = .02). Conclusions: Elite female soccer athletes are susceptible to stress fractures and menstrual dysfunction and have delayed onset of menarche despite normal BMI and appropriate body perception and attitudes towards eating. Further studies are needed to better understand stress fracture risk in female soccer athletes and in other team sports to determine how these findings relate to long‐term bone health in this population.